Acute moderate hypoxia affects the oxygen desaturation and the performance but not the oxygen uptake response - Heubert, R. A. P.; Quaresima, V.; Laffite, L. P.; Koralsztein, J. P.; Billat, V. L. (International Journal of Sports Medicine, 2005)
The purpose of this study was to examine the influence of hypoxia on the O2 uptake response, on the arterial and muscular desaturation and on the test duration and test duration at V·O2max during exhaustive exercise performed in normoxia and hypoxia at the same relative workload. Nine well-trained males cyclists performed an incremental test and an exhaustive constant power test at 90 % of maximal aerobic power on a cycling ergometer, both in normoxia and hypoxia (inspired O2 fraction = 16 %). Hypoxic normobar conditions were obtained using an Alti Trainer200 and muscular desaturation was monitored by near-infrared spectroscopy instrument (Niro-300). The mean response time (66 ± 4 s vs. 44 ± 7 s) was significantly lower in hypoxia caused by the shorter time constant of the V·O2 slow component. This result was due to the lower absolute work rate in hypoxia which decreased the amplitude of the V·O2 slow component. The arterial (94.6 ± 0.3 % vs. 84.2 ± 0.7 %) and muscular desaturation (in the vastus lateralis and the lateral gastrocnemius) were reduced by hypoxia. The test duration (440 ± 31 s vs. 362 ± 36 s) and the test duration at V·O2max (286 ± 53 s vs. 89 ± 33 s) were significantly shorter in hypoxia. Only in normoxia, the test duration was correlated with arterial and muscular saturation (r = 0.823 and r = 0.828; p < 0.05). At the same relative workload, hypoxia modified performance, arterial and muscular oxygen desaturation but not the oxygen uptake response. In normoxia, correlation showed that desaturation seems to be a limiting factor of performance.